Born abroad and educated here: Examining the impacts of education and skill mismatch among immigrant graduates in Europe - Seamus McGuinness; Delma Byrne (IZA Journal of Migration, 2015)
This paper examines the wage and job satisfaction effects of over-education and overskilling among migrants graduating from EU-15 based universities in 2005. Female migrants with shorter durations of domicile were found to have a higher likelihood of overskilling. Newly arrived migrants incurred wage penalties which were exacerbated by additional penalties resulting from overskilling in the male labour market and overeducation in the female labour market. Established migrants were found to enjoy wage premia, with no evidence of disproportionate wage impacts arising as a consequence of mismatch. Female migrants were found to have a lower probability of being job satisfied.
Keywords: J21; J31; J61; 330; Overeducation; Overskilling; Mismatch; Migrants; Gender; Pay; Job satisfaction